FORMATION OF GREEN SKILLS IN ACQUIRING PROFESSIONAL QUALIFICATIONS (Innovative professional education, 2024)
The problem of developing green skills among workers in various sectors of the economy has been updated. The role of vocational education institutions in the ecological transformation of the economy and society is revealed. The practical experience of forming green skills among those acquiring professional qualifications through the implementation of eco-oriented projects "Solar energy as a component of the educational process", "Solar benches", "Public air quality monitoring of the city of Khmelnytskyi" is presented.
Keywords: green skills, ecological culture, alternative energy, solar power plant, green professions, acquirers of professional qualifications